UNDERSTANDING FINANCIAL BEHAVIOR IN GENERATION Z - Jordan, Aireen; Nuringsih, Kartika (Graduate Program of Universitas Tarumanagara, 2023)
As the demographic growth, the presence of Generation Z or Gen-Z reached 27.94 percent in 2020 so that it dominates the demographic structure in Indonesia after the millennial generation. Gen-Z grows along with the development of information technology to form a new lifestyle that is more open to using the internet and social media than previous generations. These conditions affect financial behavior, so it is necessary to conduct a study to determine the effect of financial knowledge, financial attitudes, and self-efficacy on financial behavior. A total of 100 respondents were selected to represent Generation Z. The sample selection technique used purposive sampling with the criteria of being born in 2000-2004, currently pursuing a bachelor's degree and domicile in Jakarta. Testing the validity, reliability and data processing of structural regression equations using Smart-PLS 4. The results show the coefficient values of financial knowledge (0.271), financial attitude (0.273) and self-efficacy (0.262) where the three have a significant positive effect on financial behavior at the 5 percent level. The results of the study serve as a reference for the government in revising policies to improve financial literacy and investment models for Generation Z. Advice for related parties such as banking, insurance, investment institutions, financial services authority, and others to respect with Gen-Z in achieving sustainability in their welfare. The formation of this behavior has an impact on responsible consumption for Gen-Z circles so that long-term commitment and implementation will also support the achievement of sustainable development goals in 2030 to realize sustainable prosperity for future generations.